Sertifikasi Atas Tanah Pusaka Tinggi (Studi Nagari Ulakan, Kecamatan Ulakan Tapakis, Kabupaten Padang Pariaman, Provinsi Sumatera Barat) - Hariz Novirja Panyalai (Recital Review, 2021)
A plot of land has an important meaning and role in human life. Indonesian government has legal authority in land as it is specified in Law No. 5/1960 on Basic Regulation of Agrarian Affairs. Land Certification is used to create legal certainty in land by organizing land registration and providing certificate as evidence. There many plots of land which have not been registered such as tanah ulayat (village land), especially in Sumatera Barat Province where the majority of its people is Minangkabaunese. The reserch problems are how about the process registering tanah pusako tinggi (ancestral land) by the adat (traditional) community, how about its legal consequences, and how about its obstacles. The research used juridical normative method. Primarv data were gathered by conducting interview and secondary data were obtained from library research such as from books, journals, and electronic media. Certification of tanah pusako tinggi has the same procedure as the other land certification which is referred to the Directive of the Head of the National Land Agency No. 1/2010 on the Standard of Land Service and Regulation. However, there are some things which distinguish them from land registration in general. One of them is the right which is attached to the land is communal right. The certification causes the recognition of land rights and anything related to the control, handing out, expiration, and land acquisition as well as legal certainty on the ancestral land. Some obstacles found in the process of certification are varied, viewed from the government's few point, the internal and external factors and the people. The government has also attempted to handle the obstacles in registering tanah pusako tinggi.